The responsibility of the auditor for the evaluation of the administrative control system - محمد جبار فشاخ; مصطفى كاظمي نجف ابادي; عبد الامير نجم عبد القاضي (Iraqi Journal for Administrative Sciences, 2024)
The importance of research stems from the fact that it sheds light on administrative control and the impact of evaluating it properly on the program and objectives of the audit process. And to identify the concept of administrative control and importance and types. Learn about the responsibility of the auditor and types. Identify the importance of the system of administrative control in the work of the auditor and its impact on the development of the audit program. And identify the types of responsibilities entrusted to the auditor in general. The responses of the respondents from the sample indicate that the administrative control and accounting control are represented as one unit in order to achieve the objectives of the establishment and have an important role in achieving the goals prescribed for the establishment efficiently and effectively. There are a set of basic duties on the auditor to observe them in order to reach the results and objectives prescribed and give confirmation And the auditor is fully responsible for the examination and evaluation of the administrative control system in all its details and types that administrative control contains a set of methods and procedures necessary to achieve efficiency in the use of Of the available resources and the preservation of the property of the establishment. The auditor shall perform the necessary professional care in obtaining the information that enables him to express his opinion in the financial statements. It is necessary to find formulas for joint cooperation between the administration and the administrative control department and the auditor in order to reach the required results and achieve the objective of the audit process and ensure the proper functioning of the establishment and achieve the goals set. Achieves internal control and thus creates self-control among employees. There must be complementarity between internal control and administrative control activity in the control of any government institution. In order to achieve this integration, it is possible to control all financial transactions and fill gaps that may lead to financial and administrative corruption. And establish a sound and clear organizational structure to identify lines of authority, authority and responsibility and define functional relationships between different units. And to define a precise and clear description of all functions of the administrative unit to ensure the definition of the duties and responsibilities of each job and to facilitate the process of separating the conflicting jobs. A good system of administrative control is important for the institution, and it is also its responsibility to ensure that its application is safe.